2012
DOI: 10.1071/sh11090
|View full text |Cite
|
Sign up to set email alerts
|

University students’ perceptions of environmental risks to infertility

Abstract: This next generation of potential infertility patients exhibits a general understanding of environmental risks to infertility; however, young adults are overly optimistic that healthy lifestyle behaviours will safeguard future fertility. STIs represent the most significant modifiable risk factors for this age group; a message that can be supported by sexual and reproductive health education and promotion with greater emphasis on the long-term outcomes of STIs, including infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Previous studies reported knowledge gaps concerning fertility awareness, parenting attitudes, and specific factors influencing fertility in students in Europe [10][11][12][13][14][15][16][17], Asia [18][19][20], Africa [21], Australia [22,23], Canada [24,25], and the USA [26,27]. These studies have investigated the knowledge of young people or students, but little is known about the attitude of students towards ART and oocyte freezing as well as the differences in knowledge about fertility in special groups, e.g., medical and non-medical students and between sexes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported knowledge gaps concerning fertility awareness, parenting attitudes, and specific factors influencing fertility in students in Europe [10][11][12][13][14][15][16][17], Asia [18][19][20], Africa [21], Australia [22,23], Canada [24,25], and the USA [26,27]. These studies have investigated the knowledge of young people or students, but little is known about the attitude of students towards ART and oocyte freezing as well as the differences in knowledge about fertility in special groups, e.g., medical and non-medical students and between sexes.…”
Section: Introductionmentioning
confidence: 99%
“…Remes O . et al’s [ 8 ] semi-structured interviews showed that students had a superficial understanding of the environmental risks associated with environmental contaminants, sexually transmitted diseases and lifestyle and that at times, they relied on media reports and anecdotal information to support their beliefs. The researchers concluded that patients exhibited a general understanding of environmental risks associated with infertility but that young adults are overly optimistic that healthy lifestyle behaviors will safeguard their future fertility.…”
Section: Discussionmentioning
confidence: 99%
“…The adoption of qualitative methods is regarded as particularly useful with respect to the study of the perception of infertility, with several studies taking the approach [33][34][35]. Our qualitative study was conducted between July and September of 2019 and was based on semi-structured in-depth interviews with GPs and gynecologists.…”
Section: Designmentioning
confidence: 99%